2009
DOI: 10.1111/j.1553-2712.2009.00515.x
|View full text |Cite
|
Sign up to set email alerts
|

National Study of Patient, Visit, and Hospital Characteristics Associated With Leaving an Emergency Department Without Being Seen: Predicting LWBS

Abstract: Objectives: The objective was to estimate the national left-without-being-seen (LWBS) rate and to identify patient, visit, and institutional characteristics that predict LWBS.Methods: This was a retrospective cross-sectional analysis using the National Hospital Ambulatory Medical Care Survey (NHAMCS) from 1998 to 2006. Bivariate and multivariate analyses were performed to identify predictors of LWBS. Results:The national LWBS rate was 1.7 (95% confidence interval [CI] = 1.6 to 1.9) patients per 100 emergency d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 27 publications
4
42
2
2
Order By: Relevance
“…However, even after controlling for the correlation, triage testing continues to have a signi cant, albeit diminished, impact on abandonment, thus supporting Hypothesis 5. This con rms similar results reported in Pham et al (2009). Once the correlation is controlled for, the marginal e ect of triage testing on abandonment is quite similar across ESI levels 2, 3 and 4, ranging from -1.3 percentage points to -1.8 percentage points.…”
Section: 23supporting
confidence: 75%
“…However, even after controlling for the correlation, triage testing continues to have a signi cant, albeit diminished, impact on abandonment, thus supporting Hypothesis 5. This con rms similar results reported in Pham et al (2009). Once the correlation is controlled for, the marginal e ect of triage testing on abandonment is quite similar across ESI levels 2, 3 and 4, ranging from -1.3 percentage points to -1.8 percentage points.…”
Section: 23supporting
confidence: 75%
“…They suggested that this figure of 1.7% be used nationally by ED as a benchmark to evaluate their DNW rate. Using the figures published by Pham et al ,22 given our study's findings and acknowledging demographic variations, if our DNW patient management strategy had been employed in the ED studied over the same time period there might have been approximately 66 600 patient recalls and the possibility of 6240 subsequent admissions annually.…”
Section: Discussionmentioning
confidence: 89%
“…This study conducted in an academic teaching hospital adult ED is one of the first attempting to intervene for this specific group of patients within 24 h after they have left the hospital. A recent study conducted by Pham et al 22 in the USA showed a national DNW rate of 1.7% (1.7 per 100 visits) and a total of 1.8 million patients who left the ED before seeing a doctor. They suggested that this figure of 1.7% be used nationally by ED as a benchmark to evaluate their DNW rate.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7]27,30,43 Parmi les patients avec un code de triage de V, 27,5% (HF) et 34,2% (HD) ont fait un DAPCM. Par contre, la majorité (60%) des cas de DAPCM dans notre étude sont des patients ayant un code de triage de IV.…”
Section: Discussionunclassified
“…1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Certains DAPCM peuvent avoir des codes de triage urgents. 14,20 Les facteurs les plus souvent associés au DAPCM sont : l'achalandage de l'urgence, 5,6,[21][22][23][24] le temps d'attente jugé trop long, 4,5,9,10,17,20,[25][26][27][28][29] l'attribution d'un code de triage moins urgent, 5,6,17,20,27,[30][31][32][33] les caractéristiques intrinsèques du médecin de garde, 21,23 un jeune âge, [5][6]…”
Section: Introductionunclassified